Novitates neocaledonicae VII: A new monocaulous species of Bocquillonia (Euphorbiaceae) from New Caledonia - Bruy, David; Barrabé, Laure; Munzinger, Jérôme (Phytotaxa, 2018)
A new species of Euphorbiaceae, Bocquillonia corneri, narrowly endemic to the extreme north-east of New Caledonia’s main island, is here highlighted, described and illustrated, based on original morphological and architectural characteristics. This new species differs notably by its unique monocaulous tree habit, while other Bocquillonia species are ramified shrubs, small monocaulous shrubs or well reiterated trees. A previous identification key to Bocquillonia species is expanded to include this new species. Bocquillonia corneri is located in a very confined gully forest at low-elevation on volcano-sedimentary substrate. A preliminary IUCN conservation status of Critically Endangered (CR) is proposed.